Theoretical Analysis and Experiment of the Five DOF Hybrid Robot P(RPR/RP)RR - Xuejian Ma; Xiaoyu He; Yundou Xu; Jiantao Yao; Yongsheng Zhao (IEEE Access)
To meet the demands of machining new energy vehicles aluminum alloy structures, this paper introduced a five degree-of-freedom (DOF) hybrid robot, P(RPR/RP)RR, and conducted a systematic investigation into its kinematics, stiffness, and preliminary calibration algorithms. The research began with the robot’s kinematic model establishment. By analyzing the relationship between the independent motion variables and the branch velocities of the parallel module, a mapping matrix between input and output velocities was derived. Subsequently, the robot’s stiffness was analyzed by the coefficient matrix method. Through scale optimization, the structural dimensions of the hybrid robot are obtained. Based on three-dimensional model of the hybrid robot P(RPR/RP)RR established by these dimensions, the kinematics and stiffness of the hybrid robot are simulated and verified. Finally, the research team constructed a prototype of the robot, and zero-point error parameter calibration and accuracy testing were completed using the closed-loop vector method. This research provides significant technical support for the precision machining of aluminum alloy structures in new energy vehicles.